Pengaruh Promosi, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Oppo Smartphone Di Palembang Square Kota Palembang - Zein Ghozali; Munyati; Tutik Pebrianti; Nanda Revita; Marita Pratisila (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2022)
The aims of this study were to determine the effects of promotion, product quality and price on purchasing decisions for Oppo Smartphones in Palembang Square, Palembang City. This type of research is quantitative research. The data collection method used by researchers is purposive sampling method. Respondents in this study were 96 people. The data collection tool used in this study was a questionnaire. The data analysis tool uses the SPSS model. The conclusion from the research that can be drawn is that there is a simultaneous influence of promotion, product quality, and price on purchasing decisions for Oppo Smartphones in Palembang Square, Palembang City. The magnitude of the influence of the independent variable (Service Quality) on the dependent variable (Job Satisfaction) is 33.1%, while the remaining 66.9% is influenced by other variables, such as service quality, location and so on.